2018
DOI: 10.1055/s-0038-1676334
|View full text |Cite
|
Sign up to set email alerts
|

Management of Spontaneous CSF Rhinorrhea: An Institutional Experience

Abstract: Introduction Cerebrospinal fluid (CSF) rhinorrhea is the leakage of CSF through nasal cavity, due to abnormal communication between the arachnoid membrane and nasal mucosa. Middle-age (fourth to fifth decade) group, female gender, and obesity (body mass index > 40) are the most commonly reported risk-factors for this rare entity. In this study, we present our single center experience of spontaneous CSF rhinorrhea discussing important clinicoradiological aspects in preoperative evaluation and nuances in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…Our patient is obese, middle-aged female, this tend to be a predisposing factor for increased intracranial pressure as per previous studies [4] , [5] , [25] . The rates of spontaneous CSF leak in the US may be increased up to 2.5-fold in high obesity regions, with correlations also found between sleep apnea and hypertension in patients with CSF leak [4] , [26] .…”
Section: Discussionsupporting
confidence: 79%
“…Our patient is obese, middle-aged female, this tend to be a predisposing factor for increased intracranial pressure as per previous studies [4] , [5] , [25] . The rates of spontaneous CSF leak in the US may be increased up to 2.5-fold in high obesity regions, with correlations also found between sleep apnea and hypertension in patients with CSF leak [4] , [26] .…”
Section: Discussionsupporting
confidence: 79%
“…These rates are superior compared to the success rates of 86% in craniotomy and extracranial methods for the surgical repair of CSF leaks [ 37 ]. A review of recent studies published over the past 5 years showed a high success rate with zero or very minimal immediate postoperative complications ( Table 6 ) [ 8 , 30 , 31 , 32 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The variable success rates of endoscopic repair most likely reflect the surgeons’ technical experience, the timing of management, and the nature of the leak (high-pressure versus low-pressure).…”
Section: Discussionmentioning
confidence: 99%
“…Most CSF leaks after endoscopic removal of pituitary adenoma, if present, fall within this category. In contrast, a highflow CSF leak refers to constant CSF flow caused by direct opening of the ventricles or connection with the cisterns [42,43]. It usually occurs following an extended transsphenoidal approach or in cases of revision surgery of the recurred pituitary adenoma.…”
Section: Article In Pressmentioning
confidence: 99%